Pembuatan Website Museum Virtual Majapahit - Harison, Andreas; Liliana, Liliana; Nathania, Anita (Jurnal Infra, 2016)
Majapahit empire has so many heritages. Many heritages have different locations. Therefore it could make more difficult to learning about majapahit empire. One way to admire or learn about majapahit empireâs heritages is throughÂ a virtual website.This website will resemble most of majapahit empireâs heritages that located in different location into one location. Artefacts will be create more interesting, where the visitors can view 3 dimension object of some artefacts. This website created using some libraries, Xampp and Notepad++.Â Â Â Â Â Â Â Â Â Â Â Â Â The interface that this website use is easily understand, and user friendly. All Functions that provided also help visitors to understand more about majapahit empire.